Síntese e caracterização da metilcelulose a partir do jornal reciclado para utilização como aditivo na construção civil - Oliveira, Geandre de Carvalho (2009)
Cellulose extracted from waste newspaper was used as raw material to produce methylcellulose using dimethylsulfate (DMS). This material was characterized by the determination of the degree of substitution by chemical route, FTIR and DSC. An aqueous dispersion of methylcellulose was used to produce Portland cement (CPVARI) mortars. The results showed an increase on the consistency index with the production of a system that presented good workability, homogeneity and high viscosity, which was corroborated by the tacky aspect of the produced mixture. Hardened mortar presented an increase in the potential resistance to traction adherence when compared to the reference mortar. Those characteristics indicate that this material could be used in situations which need good workability, increasing on viscosity and adhesive properties, such as in tile installation, covering and finishing.